Oral Amelanotic Melanomas: Clinicopathologic Features of 8 Cases and Review of the Literature. (May 2021) - Soares, Ciro Dantas; Carlos, Román; Andrade, Bruno Augusto Benevenuto de; Cunha, John Lennon Silva; Agostini, Michelle; Romañach, Mário José; Hernandez-Guerrero, Juan Carlos; Mosqueda-Taylor, Adalberto; Almeida, Oslei Paes de; Jorge, Jacks
Mucosal melanomas are aggressive tumors, rarely observed in the oral cavity. The diagnosis is based on the clinical and microscopical features. Often these tumors had variable amounts of melanin pigmentation. However, when melanin is absent, the tumors are denominated amelanotic, presenting a tendency to misdiagnosis and delayed treatment. The aim of this study was to describe the clinicopathologic features of a series of oral amelanotic melanomas (OAM). Records of all cases of OAM were retrospectively retrieved from oral pathology services from January 2002 to January 2019. Data regarding the clinical features, morphological aspects, immunohistochemical reactions, treatment, and follow-up status were collected. Eight cases of OAM were included, 6 in men and 2 in women (ratio of 3:1) ranging in age from 33 to 77 years (mean 53.6 years). Clinically, the tumors presented as masses or ulcerated swellings. The most common intraoral locations of the tumors were gingiva and palate. Cervical lymph node metastasis was detected in 3 patients at the first examination. All but one patient died from complications of the tumors after a mean follow-up period of 8.5 months. In conclusion, OAM is a very aggressive malignant tumor, and when melanin is absent, an immunohistochemical panel comprising S100, melan A, HMB45, and SOX10 should be performed.